STRATEGI ISRAEL DALAM MENGHADAPI HARAKAT AT-TAHRIR AL-WATHANI AL-FILASTHINI DAN HARAKAT AL-MUQAWWATUL ISLAMIYAH - Wenni, Lisma; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Israeli-Palestinian conflict has until now become an international issue that has not yet found a definite way of peace, especially during the internal conflict between Fatah and Hamas which confronted Palestine with the separation of two different administrative areas. The difference in the response of Fatah and Hamas to Israel, made Israel had different goals and strategies against the two factions.In this study, the author will analyze why there were differences in Israel's strategy against Fatah and Hamas. The perspective used by the author in this study is realism perspective with nation state level of analysis. This study uses strategic theory that is able to explain Israel's strategy in achieving different goals against Fatah and Hamas. The qualitative method in this research uses documents from the UN Information System on the Question of Palestine, the official website of the Israel Ministry of Foreign Affairs, and the Central Elections Commission Palestine.The result of this study is that differences in ideology, strategy, and goals, where Fatah prioritizes diplomacy and Hamas used armed resistance against Israel, were the main triggers for Israel to make different strategies against the two. In its strategy, Israel used negotiations with Fatah to build cooperation, and a military strategy to destroy Hamas.Keywords : Israel, Fatah, Hamas, Israel-Palestine Conflict, Negotiations, Military Strategy